PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH KABUPATEN SUKOHARJO - Kusumawati, Salwa (JI@P, 2016)
Work performance is importance issue since the measurement of organizationalsuccess is the degree of work performance. Objective of this research isstudying the influence of leadership, work environment, and work motivationtoward civil servantsâ work performance in Sukoharjo Regency EmploymentAgency. Population of this study is all employees working in Sukoharjo RegencyEmployee Agency. Total number of the employee are 41. Quantitative researchmethodology was employed in this study. Regression statistical techniques usingsimple as well as multiple regression was used to test the hypothesis. Datashowed that leadership and work environment simultaneously influenced workperformance. Work environtment and work motivation also found simultaneouslyto have influence upon work performance. Based on F test research resultindicated that leadership, work environment, and work motivation havesimultaneously influence toward work performance. It also showed that R2 is0.949, it means that 94.9% of civil servantsâ work performance in SukoharjoRegency Employment Agency explained by leadership, work environtment, andwork motivation simultaneously.Key words: leadership; work environment; work motivation; civil servantsâ workperformance.